Comparison of Two Different Doses of Hyperbaric Bupivacaine (0.75%) in Attaining the Highest Sensory Level in Supine Versus Prone Position After Spinal Anaesthesia for Percutaneous Nephrolithotomy - MuhammadAli,MuhammadShafiq,MuhammadNabeel,MashailZahra,SehrishRiaz, MuhammadAli,MuhammadShafiq,MuhammadNabeel,MashailZahra,SehrishRiaz (Journal of Rawalpindi Medical College, 2018)
Background: To compare proportion of the patients with attainment of sensory level T4, at 5 and 10 min supine, and after 10 min prone amongst patients receiving 22.5 mg bupivacaine with those receiving 30 mg. Methods: In this randomized clinical trial patients (n=60), undergoing percutaneous nephrolithotomy, were included. It was done to compare the achievement of sensory level T4 during PCNL after spinal anaesthesia with two doses of bupivacaine before and after positioning patients in prone position. Patients were grouped into: Group A (22.5 mg hyperbaric Bupivacaine 0.75%) versus Group B (30 mg hyperbaric Bupivacaine 0.75%) consisting 30 patients each. Spinal anaesthesia was performed while sitting. Sensory level was checked using ice-cube in mid-axillary line while patients were positioned supine and prone. Results: Number of patients with T4 level at 5 min and 10 min supine in Group B was much higher than in Group A (p<0.001). In comparison of attainment of T4 level in supine and after 10 min of prone position, more number of patients achieved the level after 10 minutes of prone position in contrast to Group A and it was statistically significant (p<0.001). Conclusion: Positioning in prone extends the sensory level of spinal anaesthesia to higher level (T4) when 22.5 mg of hyperbaric bupivacaine is used and hence reduced dose can be given efficiently and safely for the procedure